FORMULATION AND CHARACTERIZATION OF ANTI-INFLAMMATORY TRANSDERMAL PATCH PREPARATIONS FROM THE EXTRACT OF PATAH TULANG (Euphorbia tirucalli) - Shandra Isasi Sutiswa; Syipa Siti Saripah; Nooryza Martihandini (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Transdermal patches are pharmaceutical preparations that aim to provide a drug delivery system across the surface of the skin and tissue, which is then delivered to the blood. is a plant that contains secondary metabolites with anti-inflammatory activity, such as alkaloids, flavonoids, polyphenols, tannins, steroids, and saponins. This study aimed to determine the characteristics of anti-inflammatory transdermal patch preparations prepared from Euphorbia tirucalli extract. The research method was laboratory experimental by preparing patches using varying concentrations of Euphorbia tirucalli extract, namely F1 (5%), F2 (10%), and F3 (15%). Next, an evaluation of patch preparation was carried out, including organoleptic tests, weight uniformity tests, thickness tests, fold durability tests, pH tests, and moisture tests. From the research results, it can be concluded that Euphorbia tirucalli extract at concentrations of 5%, 10%, and 15% can be made into patch preparations. The best characteristics of the patch preparation were F2 with an extract concentration of 10%, which had a smooth, flexible texture, folding durability >300 folds, pH 4.5, and moisture value of 7.30%.  Keywords: Anti-inflammatory, Euphorbia tirucalli, Transdermal patch